Texturing & surface characterisation of photovoltaic wafers - Ng, Chee Hong. (2013)
Solar energy is an emerging alternative to fossil fuel. Photovoltaic (PV) cells produce electricity by converting absorbed solar radiation. Hence, there are many on-going studies aimed to improve the efficiency of Photovoltaic cells. Silicon wafer is the key materials in the Photovoltaic (PV) cells. Pyramid like microscopic structures (silicon oxide’s structures after chemical etching is done) on the surface of the silicon wafer are produced by chemical etching and the gradient of these pyramids are crucial parameter in terms of light trapping capability [1]. By optimizing the gradient of these structures, highly efficient Photovoltaic cells can be fabricated.